RANCANG BANGUN SISTEM PRESENSI MAHASISWA DENGAN MENGGUNAKAN QR CODE BERBASIS ANDROID - Rahmat Gunawan; Arif Maulana Yusuf; Lysa Nopitasari (Elkom : Jurnal Elektronika dan Komputer, 2021)
Presence is an activity that aims to determine the level of attendance of a person in an agency, school or company. One of the problems that occurs is the student attendance system at STMIK Rosma Karawang due to cheating when making attendance at lecture activities begins. By looking at the problems contained in STMIK Rosma Karawang, a program is needed. To create a program requires a method. The method used is a waterfall as a software development method. The proposed database design is a DFD (Data Flow Diagram). Implementation of the program using Android Studio. With the design of the program is a solution to solve problems that exist in the presence system at STMIK Rosma Karawang, and can achieve an effective activity in supporting activities at STMIK Rosma Karawang.